Strategic and Technical Considerations in Manufacturing Viral Vector Vaccines for the Biomedical Advanced Research and Development Authority Threats - Lindsay A. Parish; Shyam Rele; Kimberly A. Hofmeyer; Brooke B. Luck; Daniel N. Wolfe (Vaccines)
Over the past few decades, the world has seen a considerable uptick in the number of new and emerging infectious disease outbreaks. The development of new vaccines, vaccine technologies, and platforms are critical to enhance our preparedness for biological threats and prevent future pandemics. Viral vectors can be an important tool in the repertoire of technologies available to develop effective vaccines against new and emerging infectious diseases. In many instances, vaccines may be needed in a reactive scenario, requiring technologies than can elicit rapid and robust immune responses with a single dose. Here, we discuss how viral vector vaccines are utilized in a vaccine portfolio for priority biological threats, some of the challenges in manufacturing viral vector vaccines, the need to strengthen live virus manufacturing capabilities, and future opportunities to capitalize on the use of viral vectors to improve the sustainability of the Biomedical Advanced Research and Development Authority’s vaccine portfolio.